The effect of cassava mosaic disease on the genetic diversity of cassava in Uganda - Kizito, Elizabeth Balyejusa; Bua, A.; Fregene, Martin A.; Egwang, T.G.; Gullberg, U. (Springer, 2005)
Cassava (Manihot esculenta) is a tropical crop that is grown in Africa, Latin America and Southeast Asia. Cassava was introduced from Latin America into West and East Africa at two independent events. In Uganda a serious threat to cassava's survival is the cassava mosaic disease (CMD). Uganda has had two notable CMD epidemics since the introduction of cassava in the 1850s causing severe losses. SSR markers were used to study the effect of CMD on the genetic diversity in five agroecologies in Uganda with high and low incidence of CMD. Surprisingly, high gene diversity was detected. Most of the diversity was found within populations, while the diversity was very small among agroecological zones and the high and low CMD incidence areas. The high genetic diversity suggests a mechanism by which diversity is maintained by the active involvement of the Ugandan farmer in continuously testing and adopting new genotypes that will serve their diverse needs. However, in spite of the high genetic diversity we found a loss of rare alleles in areas with high CMD incidence. To study the effect of the introgression history on the gene pool the genetic differentiation between East and West Africa was also studied. Genetic similarities were found between the varieties in Uganda and Tanzania in East Africa and Ghana in West Africa. Thus, there is no evidence for a differentiation of the cassava gene pool into a western and an eastern genetic lineage. However, a possible difference in the genetic constitution of the introduced cassava into East and West Africa may have been diminished by germplasm movement.